Transitions to and from formal employment and income dynamics Evidence from developing economies - Aleksynska, Mariya (OECD Development Centre Working Papers, 2023)
Using panel data for Indonesia, Malawi, Peru and South Africa, this paper investigates the relationship between transitions to formal employment and workers' labour income. It shows that transiting from informal to formal employment increases the probability of improving workers' labour income in both absolute and relative terms. However, income gains from formalisation do not accrue to all workers equally. Switching to formal employment has the greatest potential to improve the labour income of the richest workers. The chances of improving the labour income of the poorest workers through formalisation are slim. Transitions between formal and informal employment affect income gains and losses differently for men and women, older and younger workers, and workers with different levels of schooling. The effects of labour market transitions on income changes are considerably greater in magnitude than other life events such as a births, separation, or death of a partner or spouse